Molecular and Cellular Interactions of Scavenger Receptor SR-F1 With Complement C1q Provide Insights Into Its Role in the Clearance of Apoptotic Cells - Wicker-Planquart, Catherine; Dufour, Samy; Tacnet-Delorme, Pascale; Bally, Isabelle; Delneste, Yves; Frachet, Philippe; Housset, Dominique; Thielens, Nicole M. (Frontiers in Immunology, 2020)
The scavenger receptor SR-F1 binds to and mediates the internalization of a wide range of ligands, and is involved in several immunological processes. We produced recombinant SR-F1 ectodomain and fragments deleted from the last 2 or 5 C-terminal epidermal growth factor-like modules and investigated their role in the binding of acetylated low density lipoprotein (AcLDL), complement C1q, and calreticulin (CRT). C1q measured affinity was in the 100 nM range and C1q interaction occurs via its collagen-like region. We identified two different binding regions on SR-F1: the N-terminal moiety interacts with C1q and CRT whereas the C-terminal moiety binds AcLDL. The role of SR-F1 N-linked glycans was also tested by mutating each of the three glycosylated asparagines. The three mutants retained binding activities for both AcLDL and C1q. A stable THP-1 cell line overexpressing SR-F1 was generated and C1q was shown to bind more strongly to the surface of SR-F1 overexpressing macrophages, with C1q/SR-F1 colocalization observed in some membrane areas. We also observed a higher level of CRT internalization for THP-1 SR-F1 cells. Increasing SR-F1 negatively modulated the uptake of apoptotic cells. Indeed, THP-1 cells overexpressing SR-F1 displayed a lower phagocytic capacity as compared with mock-transfected cells, which could be partially restored by addition of C1q in the extracellular milieu. Our data shed some light on the role of SR-F1 in efferocytosis, through its capacity to bind C1q and CRT, two proteins involved in this process.